Structure Reassignment of Laurefurenynes A and B by Computation and Total Synthesis. Issue 38 (21st August 2013) - Shepherd, David J.; Broadwith, Phillip A.; Dyson, Bryony S.; Paton, Robert S.; Burton, Jonathan W.
<x xml:space="preserve">Abstract</x> The originally assigned stereostructures of laurefurenynes A and B have been reassigned on the basis of DFT calculations of NMR chemical shifts, synthesis of model compounds and total synthesis of laurefurenyne B, demonstrating the power of this combined approach for stereostructure elucidation/confirmation (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>